The Impact of Gender Identity on Female Offending: a Quantitative Assessment Using the BSRI - Dolliver, Matthew J. (Women & criminal justice, 2019)
Despite considerable research showing the importance of masculinity in male offending, the role of gender identity in female offending remains unclear. The current study explores the impact of gender identity on female offending among a sample of 843 college women using the Bem Sex Role Inventory and Multiple Problem Behavior Index. The impact of gender identity on rates of general deviance, as well as behaviors typically in high male and female participation, aggression and self-harming, respectively, were examined. Results found that women with masculine identity were more likely to engage in aggression as well as general deviance broadly. Gender identity was not found to impact rates of self-harming.